The of Teacher Competency, School Climate on the Implementation of Cimputer-Based National Assessment (ANBK) Mediated by Teacher Self Efficacy in State High School in Merangin Regency - Hendra Gunawan; Life Sulistyo (Universitas Muhammadiyah Enrekang, 2024)
Study This aiming For​ know influence teacher competence towards implementation Computer Based National Assessment (ANBK) for all Districts Merangin . For know influence School climate to implementation Computer Based National Assessment (ANBK) for all Districts Merangin . For know The Influence of Teacher Self Efficacy to implementation Computer Based National Assessment (ANBK) for all Districts Merangin . Research This use method data collection observation , interviews and documentation . Approach study This use quantitative that focuses on Influence Teacher Competence , School Climate to Implementation Computer -Based National Assessment (ANBK) Mediated by Teacher Self-Efficacy in State Senior High Schools throughout the Regency The wind blows . Research result show Influence Teacher competencies include : aspect personality , pedagogical , social , and professional , influential significant to implementation Computer Based National Assessment (ANBK). Competence This assist teachers in give effective teaching , motivating​ students , and understand need student during the assessment process. The influence of a positive school climate includes aspect security , relationship student -teacher, collaboration between teachers, and availability source power , in direct influence ANBK results. Supportive environment enable learning and assessment processes in progress optimally . And the level of confidence Teacher self -efficacy becomes an important mediator between teacher competency and ANBK results